Analisis Wacana Kritis Sara Mills terhadap Representasi Perempuan dalam Kasus Perceraian Tasya Farasya - Talitha; Undang Sudana (Pusat Studi Gender, Universitas Kristen Indonesia, 2025)
This study examines the representation of women's images in the phenomenon of celebrity Tasya Farasya's divorce case on social media X/Twitter. The study uses a Critical Discourse Analysis (AWK) approach from Sara Mills' perspective, emphasizing two points: the subject-object and writer-reader positions. This study uses a qualitative descriptive method with a listening and note-taking technique. The research data consists of fourteen netizen posts selected through a purposive sampling technique. The results show that Tasya Farasya is positioned as a subject with power in the discourse, while her ex-husband is positioned as an object who receives a negative image from netizens. In the writer-reader position, netizens tend to position themselves as those who support and admire Tasya Farasya as a strong, independent, and wise woman in facing divorce.